Studi Cross Sectional: Komunikasi Orang Tua Membentuk Perilaku Seksual Remaja - Agus Sri Banowo; Haristio Maulana (Fakultas Keperawatan Universitas Andalas, 2021)
Adolescent is in significant developmental transition with state of confusions and inqueries. In their development, adolescent is in a critical period of sexuality development, where adolescents will experience emotional and social development involving sexual attraction and dating. This study aims to determine the relationship between parental communication and risky sexual behavior in adolescent. This study was a quantitative study using correlative descriptive method with cross sectional design. This study used the SCS (Sexual Communication Scale) questionnaire. The results of the chi square statistical analysis showed significant value of p = 0.000 (p <0.05), it was concluded that there was a significant relationship between communication between parents and adolescents with risky sexual behavior. These results suggest that nurses with a family nursing care approach have to begin improving appropriate parental communication in facilitating care of adolescent in order to control expected sexual behavior.